Strategy "treat to target" for patients with psoriasis. Relevant issues to biological therapy persistence - A. L. Bakulev (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The review discusses the possibility of result-oriented treatment therapeutic strategy (Т2Т) for patients with psoriasis implementation, as well as analysis of the key factors to ensure stability of long-term therapy with the use of genetically engineered biological drugs. It contains data on targeted influence of inhibitor IL17A secukinumab on key factors in the immunopathogenesis of psoriasis, its efficiency and safety in treating patients with moderately-severe to severe psoriasis in the course of therapy lasting up to 3 years. It is shown that long-term usage of secukinumab with 300 mg dose once a month subcutaneously allows to reduce the severity index values and the prevalence of psoriasis PASI 90% to vast number of patients with this dermatosis, which fully corresponds to the T2T strategy. The review discusses the possibility of therapeutic response usage in the form of achieving PASI 90 as a new global goal for effective therapy for patients with psoriasis to be attained in clinical practice. We present data on immunogenicity profile of secukinumab and beneficial impact on efficiency, as well as on safety of treatment with the usage of this genetically engineered biological medication.